Análisis del patrón facial y su relación con la sonrisa en usuarios que concurren a la organización internacional de policía criminal interpol Perú, sede descentralizada Arequipa, Perú - Vizcarra Zorrilla, Fernando Claudio (2020)
Aim: To analyze facial patterns and their relationship with the smile in users at the decentralized headquarters of the International Criminal Police Organization INTERPOL in Arequipa, Peru in 2018. Materials and methods: A sample of 72 individuals between 20 and 40 years old was selected, in whom the facial morphological index was obtained, and the facial pattern was determined. Three posed smile photographs were taken to analyze the smile components: oral corridor, frontal occlusal plane, smile arch, lip line, curvature of the upper lip; symmetry of the smile and dental and gingival components. The data were analyzed using the Fisher's exact test or Chi square test to establish associations among variables. Results: The euryprosopo facial pattern presents a low smile line (50%) and average smile line (45.8%), while mesoprosopo and leptoprosopo facial patterns present an average smile line (54.2% and 50.0% respectively). Euryprosopo and mesoprosopo facial patterns have an unacceptable occlusal frontal plane (58.3% and 54.2% respectively), and the leptoprosopo facial pattern has an acceptable occlusal frontal plane (58.3%). The remaining smile components are similar among the three facial patterns. Conclusions: The results obtained establish that there is no association between facial patterns and smile components. In the absence of statistically significant values (p > 0.05), there is not enough evidence to conclude that the variables are associated.